2010
DOI: 10.1097/mbc.0b013e328339cc1c
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient lentiviral transduction of phenotypically and genotypically characterized endothelial progenitor cells from adult peripheral blood

Abstract: Postnatal vasculogenesis has been implicated as an important mechanism for neovascularization via bone marrow-derived endothelial progenitor cells (EPCs) circulating in peripheral blood. In preparation of the utilization of EPCs in clinical protocols, we have generated blood-derived EPCs according to two established protocols by culturing either nonadherent mononuclear cells on fibronectin or adherent mononuclear cells on collagen. To explore the feasibility of these EPCs for their potential clinical use as ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…From our findings, the present method achieved a transduction efficiency greater than 93% TdTomato positive cells. Such a high fluorescence yield is a result consistent with that of Stockschlaeder (19), who achieved gene transfer efficiency of up to 99% with endothelial progenitor cell from adult peripheral blood. Yockell-Lelievre et al (17) reported an average transduction efficiency of 68% in human umbilical vein endothelial cells (HUVECs) as well as in human aortic endothelial cells and human microvascular endothelial cells using a double-pulse electroporation method.…”
Section: Discussionsupporting
confidence: 88%
“…From our findings, the present method achieved a transduction efficiency greater than 93% TdTomato positive cells. Such a high fluorescence yield is a result consistent with that of Stockschlaeder (19), who achieved gene transfer efficiency of up to 99% with endothelial progenitor cell from adult peripheral blood. Yockell-Lelievre et al (17) reported an average transduction efficiency of 68% in human umbilical vein endothelial cells (HUVECs) as well as in human aortic endothelial cells and human microvascular endothelial cells using a double-pulse electroporation method.…”
Section: Discussionsupporting
confidence: 88%
“…Increasing MOI to 10 and 60 resulted in 80% and 88% transduction efficiency, respectively (De Meyer et al, 2006;van den Biggelaar et al, 2009). The transduction efficiency could be improved to as high as 96% when using a lentiviral vector LeGo with an SFFV-U3-derived internal promoter (Stockschlaeder et al, 2010), demonstrating that transduction efficiencies may vary significantly depending on the particular viral vector, internal promoter, and particularly the MOI used. In addition, we found that transduction efficiency could also be improved from 47% to 79% when transducing EPC colonies containing fewer cells, suggesting that transduction of isolated EPC colonies as early as possible could be an improved way to obtain a large population of transduced EPCs.…”
Section: Discussionmentioning
confidence: 82%